Analisis Gaya Kepemimpinan Situasional dalam Kemajuan Pembangunan Infrastruktur Daerah - Desri, Suryatman; Fikri, Ahmad; Ulfa, Srimaria (Al-DYAS, 2023)
Leadership is an individual action that can have an impact on the community (regional heads have an impact on the community) in order to get support for village development goals. The ability of a leader to influence his followers and persuade them to work according to his instructions is referred to as a leader's style. A philosophy called situational leadership places a strong emphasis on the state of followers or subordinates. Use research techniques to gather scientific knowledge carefully by gathering sources from research literature found in various scientific journals. Consultative and participatory leadership styles are among the many styles available in situational leadership. Both suggest that if leadership has been used, especially in development that is supported by a transparent development plan and carried out in accordance with established pathways and processes.